Entanglements of feminist activism and gender equality policy in the Spanish and Swedish film industries: between convergence and critique. - Jansson, Maria; Calderón-Sandoval, Orianna (Journal of Gender Studies, 2024)
This article compares entanglements between activist demands and policy in the Spanish and Swedish film industries using a critical frames approach. Considering contextual factors such as domestic discourse on film policy and resistance against gender equality, the comparison is based on deep insider knowledge aiming to deepen the understanding of feminist activism and its relation to policy in the two countries. In both Spain and Sweden, activists have demanded equality in the film sector since the seventies. Today, both countries feature gender equality measures and vivid feminist organizations. Based on current equality policies, reports from the Swedish and Spanish Film Institutes, documents from feminist filmmakers' associations and interviews with activists, the article shows that feminist activists oscillate between strategically converging their demands to policy and criticizing reforms. Furthermore, policy echoes activists' arguments but are less informed by ideas about structural inequalities. Activists in both Spain and Sweden stand up for the gender equality measures which have been implemented, but the Spanish activists are more prone to simultaneously voice criticism against the reforms..